ROBOTIC CATHETER ABLATION OF PERSISTENT ATRIAL FIBRILLATION (RANDOMIZED TRIAL RESULTS) - M. A. Naymushin; D. S. Lebedev (Российский кардиологический журнал)
Aim. Comparison of efficacy and safety of the robotic catheter and manual catheter ablation in management of patients with persistent atrial fibrillation (PsAF).Material and methods. In the study, 80 patients included, with PsAF. They were randomized to groups of manual ablation (MA) and robotic ablation (RA). After ablation, patients were followed up during 1 year every 3 months. Sinus rhythm retention was evaluated with Holter 24-hour ECG monitoring and 12-channel ECG. As efficacy criteria, the absence was taken of registered paroxysms of atrial fibrillation and other tachiarrhythmias lasted 30 sec and more. As primary endpoint, the absence was taken of any atrial tachiarrhythmias (AFib/AFlut) after the ablation procedure during 12 months, with every 3 months ECG monitoring. As secondary endpoints the following were taken: complications rate, duration of procedure and x-ray exposition, rate of recovery of conduction through the ablation line in acute phase (in 30 min post ablation) with intravenous ATP.Results. Mean procedure time and x-rays exposition in MA group was 164±28 min and 45±14 min, respectively. Mean duration of procedure in RA was 200±35 min (p<0,05). However x-ray duration was lower in RA group: 30±12 min, and the time of rentgenoscopy per operator was even lower: 18±6 min (p<0,05) In the MA group, in 9 (25%) patients there was recovery of conduction through the border, with ATP injection at acute stage, and in RA group — in two patients (5%), p<0,05. Total number of adverse events did not differ in groups (p=0,5).Conclusion. RA in patients with PsAF makes in to effectively isolate pulmonary veins ostia during the surgery, and to block the conduction through the borderline. The percentage of major and minor adverse events in acute and chronic period of RA is not higher than that in MA and is 10%. Application of RA makes it to decrease x-ray exposition per operator 2,5 times, and on a patient — by 30%. Training period in RA is 10 operations that is significantly lower than in MA.